A SOCIOLINGUISTIC STUDY OF COMPLIMENT RESPONSES AMONG AMERICANS AND INDONESIANS AND ITS IMPLICATIONS FOR TEACHING ENGLISH - Ibrahim, Jusuf; J. Riyanto, Theophilus (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
The writers in this study would like to find out whether there is any difference between Indonesians and Americans in responding to compliments. This study also attempts to discover whether both the Americans and Indonesians in this study show a preference for certain types of compliment responses. Lastly, it also tries to see if a certain variable like status can play a role in determining the types of compliment responses chosen. To collect the data, the writers use the elicitation method. They use two sets of role-play consisting of four situations made as close as possible to the real-life situations. The first is for the Indonesian respondents; the other for the Americans. The respondents are asked to respond to the situations and their responses are then recorded on the tape for further analysis. The data are then analyzed using Herbert's Twelve Types of Compliment Responses. The research finds that both the Indonesians and Americans show differences in responding to Compliments. They are different in terms of both the types of Compliment Responses chosen and the frequencies made. The findings also reveal that status is an important variable affecting the choice of a particular response.